Negative electrode sheet and preparation method thereof, secondary battery, battery module, battery pack and power-consuming device

By using a negative electrode protective layer of a composite carbon material with a two-dimensional/three-dimensional composite structure and a highly lithium-philic composite carbon material in the negative electrode sheet, the problem of loss of active lithium in the charging and discharging of lithium-ion batteries is solved, and the secondary battery is significantly improved cycling performance.

CN115832242BActive Publication Date: 2025-02-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210846140.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-19
Publication Date
2025-02-25
Estimated Expiration
2042-07-19

AI Technical Summary

Technical Problem

The loss of active lithium during the charging and discharging of lithium-ion batteries leads to a decrease in the capacity of the secondary battery and deterioration of the negative electrode plate circulation performance.

Method used

Using a negative electrode protective layer containing a specific composite carbon material, the composite carbon material has a two-dimensional/three-dimensional composite structure and high lithium-philicity, reducing lithium-ion surface of the negative electrode sheet, thereby improving the circulation performance of the secondary battery.

Benefits of technology

By reducing lithium surface of the negative electrode sheet, the circulation performance of the secondary battery is improved and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115832242B_ABST
    Figure CN115832242B_ABST
Patent Text Reader

Abstract

The present application provides a negative electrode plate, comprising: a negative electrode current collector, a negative electrode active material layer and a negative electrode protective layer. The negative electrode active material layer is arranged on at least one surface of the negative electrode current collector. The negative electrode protective layer is arranged on the surface of the negative electrode active material layer away from the negative electrode current collector; the negative electrode protective layer comprises a composite carbon material; the composite carbon material comprises a MXene material and a three-dimensional inorganic carbon material, and the three-dimensional inorganic carbon material contains a metal oxide. The negative electrode plate is provided with a negative electrode protective layer comprising a specific composite carbon material, and the composite carbon material has a two-dimensional / three-dimensional composite structure and a high lithium affinity, which can reduce lithium deposition on the surface of the negative electrode plate, and the secondary battery has good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode plate and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device. Background Art

[0002] Lithium-ion batteries are secondary batteries that rely on the movement of lithium ions between the positive and negative electrodes. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + It is deintercalated from the positive electrode and then embedded into the negative electrode through the electrolyte, so that the negative electrode is in a lithium-rich state; the opposite is true during discharge. During the charge and discharge process, the loss of active lithium in lithium-ion batteries not only affects the capacity of the secondary battery, but also causes the deterioration of the negative electrode sheet, affecting the cycle performance. Summary of the invention

[0003] Based on the above problems, the present application provides a negative electrode plate and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device, which can improve the cycle performance of the secondary battery.

[0004] In one aspect of the present application, a negative electrode plate is provided, comprising:

[0005] Anode current collector;

[0006] a negative electrode active material layer, the negative electrode active material layer being disposed on at least one surface of the negative electrode current collector; and

[0007] A negative electrode protection layer, wherein the negative electrode protection layer is arranged on the surface of the negative electrode active material layer away from the negative electrode current collector; the negative electrode protection layer comprises a composite carbon material; the composite carbon material comprises a MXene material and a three-dimensional inorganic carbon material, and the three-dimensional inorganic carbon material contains a metal oxide.

[0008] The negative electrode plate of the present application is provided with a negative electrode protective layer comprising a specific composite carbon material. The composite carbon material has a two-dimensional / three-dimensional composite structure and a high lithium affinity, which can reduce lithium deposition on the surface of the negative electrode plate, and the secondary battery has good cycle performance.

[0009] In some embodiments, the MXene material comprises Ti3C2T x 、Ti4C3Tx、Ti2CT x 、V2CT x and Nb2CT x At least one of which T x represents the functional group of MXene material, T x including -OH; optionally, T x It also includes at least one of =O, -F and -Cl.

[0010] In some embodiments, the three-dimensional inorganic carbon material contains a carboxyl group, and the Mxene material is connected to the three-dimensional inorganic carbon material through an ester bond. The Mxene material and the three-dimensional inorganic carbon material are covalently connected through an ester bond, and have a stable two-dimensional / three-dimensional composite structure in the negative electrode protective layer, which can improve lithium ion transmission, avoid lithium precipitation on the surface of the negative electrode plate, and improve the cycle performance of the secondary battery.

[0011] In some embodiments, the specific surface area of ​​the composite carbon material is 26 m 2 / g~67m 2 / g, optional 26.92m 2 / g~66.04m 2 / g.

[0012] In some of the embodiments, the pore size of the composite carbon material is 5 nm to 21 nm, and can be optionally 5.2 nm to 20.1 nm.

[0013] The above-mentioned composite carbon material has a high specific surface area and rich pore structure, which is conducive to improving lithium ion transmission, and can fix dead lithium such as lithium dendrites in the negative electrode protective layer, avoiding problems such as powdering and expansion of the negative electrode sheet caused by dead lithium such as lithium dendrites.

[0014] In some embodiments, the metal oxide includes at least one of TiO2, ZnO, Fe3O4, Cr2O3, ZrO2 and CuO;

[0015] Optionally, the metal oxide is TiO2.

[0016] The above-mentioned metal oxide has good lithium affinity, which can improve the wettability of the negative electrode plate to lithium ions, thereby improving the transmission of lithium ions and reducing the internal resistance of the secondary battery.

[0017] In some embodiments, in the negative electrode protection layer, the mass percentage of the composite carbon material is 90% to 98%; optionally, in the negative electrode protection layer, the mass percentage of the composite carbon material is 96% to 97.5%. When the mass content of the composite carbon material in the negative electrode protection layer is within the above range, the negative electrode plate can effectively reduce surface lithium deposition, and the secondary battery has good cycle performance.

[0018] In some embodiments, the raw materials for preparing the composite carbon material include the Mxene material and the metal organic framework material. The Mxene material is an inorganic compound with a two-dimensional structure, and the metal organic framework material is an organic-inorganic hybrid material with intramolecular pores formed by self-assembly of organic ligands and metal ions or clusters through coordination bonds. The composite carbon material prepared from the Mxene material and the metal organic framework material has the two-dimensional / three-dimensional skeleton structure of the Mxene material and the metal organic framework material, and contains metal oxides. The composite carbon material has a large specific surface area and good lithium affinity.

[0019] In some embodiments, the mass ratio of the Mxene material to the metal organic framework material is (0.1-0.5): 1; optionally, the mass ratio of the Mxene material to the metal organic framework material is (0.2-0.4): 1. When the mass ratio of the Mxene material to the metal organic framework material is within the above range, the composite carbon material has a more suitable two-dimensional / three-dimensional skeleton structure, which can effectively inhibit the expansion of the negative electrode sheet while improving the lithium deposition on the negative electrode surface, and the cycle performance of the secondary battery is better.

[0020] In some embodiments, the metal center of the metal organic framework material includes at least one of Ti, Fe, Cu, Zr, Zn and Cr;

[0021] Optionally, the metal center is Ti.

[0022] The above-mentioned metal elements have good lithium affinity, and the corresponding metal oxides contained in the prepared composite carbon material can effectively improve the lithium ion transmission in the negative electrode plate and reduce lithium deposition on the negative electrode surface.

[0023] In some embodiments, the organic ligand of the metal organic framework material includes at least one of terephthalic acid and trimesic acid;

[0024] Optionally, the organic ligand is terephthalic acid.

[0025] In some embodiments, the metal organic framework material includes at least one of MIL-125, MOF-5, MIL-88B, MIL-100, MIL-101, UiO-66 and HKUST-1;

[0026] Optionally, the metal organic framework material is MIL-125.

[0027] In some embodiments, the method for preparing the composite carbon material comprises the following steps:

[0028] Mixing the MXene material and the metal organic framework material to prepare an intermediate;

[0029] The intermediate is pyrolyzed at 250° C. to 500° C. under a protective atmosphere to prepare the composite carbon material.

[0030] In the preparation method of the above-mentioned composite carbon material, MXene material and metal organic framework material are mixed to obtain an intermediate with a suitable two-dimensional / three-dimensional skeleton structure. The organic ligands in the metal organic framework material are carbonized by pyrolysis to form amorphous carbon. The obtained composite carbon material still retains the skeleton structure of the MXene material and the metal organic framework material, which can effectively reduce lithium deposition on the surface of the negative electrode.

[0031] In some embodiments, the thickness of the negative electrode protection layer is L1, the total thickness of the negative electrode protection layer and the negative electrode active material layer is L2, and the negative electrode plate satisfies: 0.05≤L1 / L2≤0.4.

[0032] In some embodiments, the thickness L1 of the negative electrode protection layer is 8 μm to 15 μm; optionally 10 μm to 14 μm.

[0033] When the thickness of the negative electrode protection layer and its proportion are within the above range, while ensuring the energy density, lithium is not easily deposited on the surface of the negative electrode plate, thereby improving the cycle performance of the secondary battery.

[0034] In a second aspect, the present application further provides a method for preparing the negative electrode sheet of the first aspect, comprising the following steps:

[0035] preparing a negative electrode protective layer slurry, wherein the negative electrode protective layer slurry contains the composite carbon material;

[0036] The negative electrode protection layer slurry is used to form the negative electrode protection layer on the surface of the negative electrode active material layer away from the negative electrode current collector.

[0037] In a third aspect, the present application further provides a secondary battery, comprising the negative electrode plate of the first aspect.

[0038] In a fourth aspect, the present application further provides a battery module, comprising the secondary battery of the third aspect.

[0039] In a fifth aspect, the present application also provides a battery pack, comprising at least one of the secondary battery of the third aspect and the battery module of the fourth aspect.

[0040] In a sixth aspect, the present application further provides an electrical device comprising at least one selected from the secondary battery of the third aspect, the battery module of the fourth aspect, and the battery pack of the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0042] Figure 1 A schematic diagram of a secondary battery according to an embodiment of the present application;

[0043] Figure 2 for Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;

[0044] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0045] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application;

[0046] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0047] Figure 6 A schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source;

[0048] Description of reference numerals:

[0049] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION

[0050] Below, the negative electrode plate and its preparation method, secondary battery, battery module, battery pack and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0051] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0052] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0053] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0054] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0055] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0056] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0057] The secondary battery, battery module, battery pack, and electric device of the present application are described below with reference to the accompanying drawings as appropriate.

[0058] In one embodiment of the present application, a secondary battery is provided.

[0059] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0060] Negative electrode

[0061] The negative electrode sheet includes a negative electrode current collector, a negative electrode active material layer and a negative electrode protective layer. The negative electrode active material layer is disposed on at least one surface of the negative electrode current collector. The negative electrode protective layer is disposed on the surface of the negative electrode active material layer away from the negative electrode current collector. The negative electrode protective layer includes a composite carbon material; the composite carbon material includes a MXene material and a three-dimensional inorganic carbon material, and the three-dimensional inorganic carbon material contains a metal oxide.

[0062] The negative electrode plate of the present application is provided with a negative electrode protective layer comprising a specific composite carbon material. The composite carbon material has a two-dimensional / three-dimensional composite structure and a high lithium affinity, which can reduce lithium deposition on the surface of the negative electrode plate, and the secondary battery has good cycle performance.

[0063] MXene materials are a class of inorganic compounds with a two-dimensional structure, composed of transition metal carbides, nitrides or carbonitrides with a thickness of several atomic layers. MXene materials have excellent conductivity, low lithium ion diffusion barrier and abundant lithium-philic functional groups, and have high strength and flexibility. Compared with traditional two-dimensional carbon materials, MXene materials have better lithium affinity and a much higher density than traditional carbon materials. They are used to prepare negative electrode plates without affecting the compaction density of the plates.

[0064] The above-mentioned three-dimensional inorganic carbon material containing metal oxide has a three-dimensional skeleton structure and contains metal oxide, which can further improve the lithium ion transmission of the negative electrode plate. Compared with traditional three-dimensional carbon materials, it is more conducive to improving lithium ion transmission.

[0065] The composite carbon material including the MXene material and the three-dimensional inorganic carbon material is used to prepare the negative electrode protective layer, which can effectively improve the lithium deposition on the negative electrode surface and improve the cycle performance of the secondary battery.

[0066] In some embodiments, the MXene material includes Ti3C2T x 、Ti4C3Tx、Ti2CT x 、V2CT x and Nb2CT x At least one of which T x represents the functional group of MXene material, T x Including -OH. Optionally, T x The MXene material further comprises at least one of =O, -F and -Cl. x .

[0067] In some embodiments, the three-dimensional inorganic carbon material contains a carboxyl group, and the Mxene material is connected to the three-dimensional inorganic carbon material through an ester bond. The Mxene material is covalently connected to the three-dimensional inorganic carbon material through an ester bond, and has a stable two-dimensional / three-dimensional skeleton structure in the negative electrode protective layer, which can improve lithium ion transmission, avoid lithium precipitation on the surface of the negative electrode plate, and improve the cycle expansion of the negative electrode plate, and the cycle performance of the secondary battery is better.

[0068] In some embodiments, the specific surface area of ​​the composite carbon material is 26 m 2 / g~67m 2 / g. Optionally, the specific surface area of ​​the composite carbon material is 26.92m 2 / g~66.04m 2 / g. The specific surface area of ​​the composite carbon material can be in the range of any of the following values: 26m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g, 55m 2 / g, 60m 2 / g, 65m 2 / g or 67m 2 / g. Specific surface area refers to the total area per unit mass of a material. The specific surface area can be tested by methods well known to those skilled in the art. As an example, the specific surface area of ​​a composite carbon material can be calculated by a multi-point Brunauer-Emmett-Teller method after measuring the nitrogen isothermal adsorption-desorption curve of the material using a fully automatic gas adsorption analyzer.

[0069] In some embodiments, the pore size of the composite carbon material is 5nm to 21nm, and optionally, the pore size of the composite carbon material is 5.2nm to 20.1nm. The pore size of the composite carbon material can be in the range of any of the following numerical values: 5nm, 6nm, 8nm, 10nm, 12nm, 15nm, 18nm, 20nm or 21nm. The pore size of the composite carbon material refers to the average pore size of the composite carbon material, which is a well-known meaning in the art and can be tested by methods known in the art. The average pore size evaluation method refers to GB / T 19587-2017 and GB / T 21650.2-2008, and is tested using a TriStar 3020 pore size distribution instrument. At a constant temperature, the adsorbed gas is adsorbed on the material to be tested under a series of gradually increasing pressures. The pore size distribution of the composite carbon material can be characterized by the volume of each pore size and the corresponding partial pressure curve; at the same time, the average pore size can be calculated.

[0070] The above-mentioned composite carbon material has a high specific surface area and rich pore structure, which is conducive to improving lithium ion transmission, and can fix dead lithium such as lithium dendrites in the negative electrode protective layer, avoiding problems such as powdering and expansion of the negative electrode sheet caused by dead lithium such as lithium dendrites.

[0071] In some embodiments, the metal oxide includes at least one of TiO2, ZnO, Fe3O4, Cr2O3, ZrO2 and CuO; optionally, the metal oxide is TiO2. The above metal oxides have good lithium affinity, which can improve the wettability of the negative electrode plate to lithium ions, thereby improving the transmission of lithium ions and reducing the internal resistance of the secondary battery.

[0072] In some of the embodiments, the raw materials for preparing the composite carbon material include Mxene materials and metal organic framework materials. Mxene materials are inorganic compounds with a two-dimensional structure, and metal organic framework materials are organic-inorganic hybrid materials with intramolecular pores formed by self-assembly of organic ligands and metal ions or clusters through coordination bonds. The composite carbon material prepared from Mxene materials and metal organic framework materials has the two-dimensional / three-dimensional skeleton structure of Mxene materials and metal organic framework materials, and contains metal oxides. The composite carbon material has a large specific surface area and good lithium affinity.

[0073] In some embodiments, the mass ratio of the Mxene material to the metal organic framework material is (0.1-0.5): 1; optionally, the mass ratio of the Mxene material to the metal organic framework material is (0.2-0.4): 1. When the mass ratio of the Mxene material to the metal organic framework material is within the above range, the composite carbon material has a more suitable two-dimensional / three-dimensional skeleton structure, which can effectively inhibit the expansion of the negative electrode sheet while improving the lithium deposition on the negative electrode surface, and the cycle performance of the secondary battery is better.

[0074] In some of the embodiments, the metal center of the metal organic framework material includes at least one of Ti, Fe, Cu, Zr, Zn and Cr; optionally, the metal center is Ti.

[0075] The above-mentioned metal elements have good lithium affinity, and the corresponding metal oxides contained in the prepared composite carbon material can effectively improve the lithium ion transmission in the negative electrode plate and reduce lithium deposition on the negative electrode surface.

[0076] In some of the embodiments, the organic ligand of the metal organic framework material includes at least one of terephthalic acid and trimesic acid; optionally, the organic ligand is terephthalic acid.

[0077] In some of the embodiments, the metal organic framework material includes at least one of MIL-125, MOF-5, MIL-88B, MIL-100, MIL-101, UiO-66 and HKUST-1; optionally, the metal organic framework material is MIL-125.

[0078] In some embodiments, the method for preparing the composite carbon material includes the following steps S110 and S120:

[0079] S110: Mixing MXene materials and metal organic framework materials to prepare an intermediate.

[0080] S120: Pyrolyze the intermediate at 250°C to 500°C under a protective atmosphere to prepare a composite carbon material. Optionally, the pyrolysis temperature can be in the range of any of the following numerical values: 250°C, 300°C, 350°C, 400°C, 450°C or 500°C. Further, the pyrolysis temperature is 400°C to 500°C. If the pyrolysis temperature is too low, the organic ligands of the metal organic framework material are not sufficient to be carbonized to form an inorganic carbon material; if the pyrolysis temperature is too high, the three-dimensional inorganic carbon material formed by carbonization does not contain carboxyl groups.

[0081] In the preparation method of the above-mentioned composite carbon material, MXene material and metal-organic framework material are mixed to obtain an intermediate with a suitable two-dimensional / three-dimensional skeleton structure. The organic ligands in the metal-organic framework material are carbonized by pyrolysis to form carboxyl-rich amorphous carbon. The obtained composite carbon material still retains the skeleton structure of the MXene material and the metal-organic framework material, which can effectively reduce lithium deposition on the surface of the negative electrode.

[0082] In some embodiments, the thickness of the negative electrode protective layer is L1, the total thickness of the negative electrode protective layer and the negative electrode active material layer is L2, and the negative electrode plate satisfies: 0.05≤L1 / L2≤0.4. Further, 0.1≤L1 / L2≤0.4. In some embodiments, the thickness of the negative electrode protective layer is 8μm to 15μm. Optionally, the thickness of the negative electrode protective layer is 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm. Further, the thickness of the negative electrode protective layer is 10μm to 14μm. The thickness of the negative electrode protective layer and the thickness ratio of the negative electrode protective layer to the negative electrode active material layer are within the above range. While ensuring the energy density, lithium is not easily deposited on the surface of the negative electrode plate, thereby improving the cycle performance of the secondary battery.

[0083] As an example, the thickness of the negative electrode protective layer and the negative electrode active material layer can be tested according to the following method: the cold pressed negative electrode sheet is cut into samples of 6cm*6cm size, and then polished with an IB-19500CP ion cross-section polisher to obtain a polished sample with a cut surface. Then, the sample is tested with a ZEISS sigma 300 device in accordance with the standard JY / T010-1996. Ten different positions are randomly selected from the test sample for testing, and the average value is taken to obtain the thickness of the negative electrode protective layer, the negative electrode active material layer and their total thickness.

[0084] In some embodiments, in the negative electrode protective layer, the mass percentage of the composite carbon material is 90% to 98%. Optionally, in the negative electrode protective layer, the mass percentage of the composite carbon material can be in the range of any of the following numerical values: 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%. Further, in the negative electrode protective layer, the mass percentage of the composite carbon material is 96% to 97.5%. When the mass content of the composite carbon material in the negative electrode protective layer is within the above range, the negative electrode plate can effectively reduce surface lithium deposition, and the secondary battery has good cycle performance.

[0085] In some embodiments, the negative electrode protective layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0086] In some embodiments, the negative electrode protection layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0087] In some of the embodiments, the negative electrode protection layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0088] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on any one or both of the two facing surfaces of the negative electrode current collector.

[0089] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate. The polymer material substrate includes substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0090] In some of the embodiments, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0091] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0092] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0093] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0094] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as composite carbon material, negative electrode active material, conductive agent, binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode active material layer slurry and a negative electrode protective layer slurry; the negative electrode active material layer slurry is coated on the negative electrode current collector to form a negative electrode active material layer; the negative electrode protective layer slurry is coated on the surface of the negative electrode active material layer to form a negative electrode protective layer; after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0095] Positive electrode

[0096] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.

[0097] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0098] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate. The polymer material substrate includes substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0099] In some of the embodiments, the positive electrode active material may adopt the positive electrode active material for batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0100] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0101] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0102] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0103] Electrolytes

[0104] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0105] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0106] In some of the embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.

[0107] In some of the embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0108] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0109] Isolation film

[0110] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0111] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular limitation.

[0112] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0113] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0114] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.

[0115] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0116] In some of these embodiments, reference Figure 2 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0117] In some of the embodiments, the secondary batteries may be assembled into a battery module. The number of the secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0118] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0119] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0120] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. The specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0121] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0122] In addition, the present application also provides an electrical device, which includes at least one of the secondary batteries, battery modules, or battery packs provided in the present application. The secondary batteries, battery modules, or battery packs can be used as power sources for electrical devices, and can also be used as energy storage units for electrical devices. Electrical devices may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited to these. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0123] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0124] Figure 6 The power consumption device 6 is taken as an example. The power consumption device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0125] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0126] Example

[0127] The following are examples of the present application. The examples described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or in the product instructions are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially. The following examples are mainly for the composite carbon material Ti3C2T x / TiO2@C, it can be understood that in other specific embodiments, the composite carbon material in the negative electrode sheet is not limited to Ti3C2T x / TiO2@C.

[0128] Embodiment 1:

[0129] (1) Preparation of composite carbon materials:

[0130] (1.1)Ti3C2T x Material preparation: 0.8 g LiF was added to 10 mL 9 M HCl aqueous solution and then stirred for 10 min. Subsequently, 0.5 g TiAlC was slowly added to the above etching solution at room temperature and kept stirring for 24 h. The acidic mixture was repeatedly washed with deionized water and centrifuged until the pH was ≈6. A stable dark green supernatant was observed after centrifugation at 3500 rpm for 1 h. Finally, the resulting suspension was freeze-dried for 2 days to obtain Ti3C2T x Nanosheets.

[0131] (1.2) Preparation of MIL-125: 3 g of 1,4-phthalic acid was dissolved in 54 mL of N,N'-dimethylformamide, and then 6 g of tetrabutyl titanate and 6 mL of methanol were added at room temperature with stirring until a clear solution was uniformly dispersed. The solution was then placed in a 100 mL polytetrafluoroethylene-lined autoclave at 150 °C for 24 hours. The resulting white solid was recovered by filtration at room temperature and washed several times with acetone to remove solvent molecules from the pores. Finally, it was dried in a vacuum oven at 60 °C overnight.

[0132] (1.3)Ti3C2T x / TiO2@C preparation: MIL-125 was added to 50 mL of Ti3C2T x Ti3C2T x The mass ratio of Ti3C2T to MIL-125 was 0.3:1. Then, the solution was ultrasonicated for 1 h to obtain a uniform solution. The collected solution was freeze-dried for 2 days to obtain Ti3C2T x / MIL-125 composites. Then, Ti3C2T x / MIL-125 composite material was pyrolyzed at 500℃ (heating rate 5℃ / min) (MIL-125 pyrolysis gave TiO2@C hybrid, which was rich in carboxyl groups and had a strong affinity with Ti3C2T x Through ester bond connection), Ti3C2T x / TiO2@C hybrid. The Ti3C2T prepared in this example x The specific surface area of ​​the TiO2@C material is 49.55 m 2 / g, and the pore size is 14.1nm.

[0133] (2) Preparation of negative electrode sheet: Active material artificial graphite, silicon oxide, conductive agent carbon black, binder styrene butadiene rubber (SBR), and thickener sodium hydroxymethyl cellulose (CMC) were dissolved in deionized water according to a mass ratio of 72.3:24.9:0.8:0.8:1.2, mixed evenly to prepare negative electrode slurry, coated on the negative electrode current collector copper foil, and dried to prepare the negative electrode active material layer.x / TiO2@C, conductive agent carbon black, binder styrene butadiene rubber (SBR), and thickener sodium hydroxymethyl cellulose (CMC) are dissolved in deionized water according to a mass ratio of 96.2:0.8:0.8:1.2, and mixed evenly to prepare a protective layer slurry; the protective layer slurry is coated on the negative electrode sheet, and the negative electrode sheet with a protective layer is obtained after drying, cold pressing, and cutting. The thickness L1 of the negative electrode protective layer is 10μm, the total thickness L2 of the negative electrode protective layer and the negative electrode active material layer is 100μm, and L1 / L2 is 0.1.

[0134] (3) Preparation of positive electrode sheet: The positive electrode active material NCM811, the conductive agent carbon black, the binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were stirred and mixed in a mass ratio of 95.84:1.47:1.55:1.14 to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode collector, and then dried, cold pressed and cut to obtain a positive electrode sheet.

[0135] (4) Preparation of electrolyte: In an argon atmosphere glove box, organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) / diethyl carbonate (DEC) were mixed in a volume ratio of 36:29:35, 1 M LiPF6 lithium salt was added and dissolved in the organic solvent, and the mixture was stirred to obtain an electrolyte.

[0136] (5) Preparation of secondary batteries: Using polypropylene film as a separator, stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets to play a role of isolation, and then wind to obtain a bare cell, weld the tabs to the bare cell, and put the bare cell into an aluminum shell, and bake at 80°C to remove water, then inject electrolyte and seal to obtain an uncharged battery. The uncharged battery then goes through the processes of static, hot and cold pressing, formation, shaping, capacity testing, etc. to obtain a secondary battery product.

[0137] Embodiment 2:

[0138] The difference between Example 2 and Example 1 is that (1.3) Ti3C2T x / TiO2@C in the preparation of Ti3C2T x The mass ratio of Ti3C2T to MIL-125 is 0.1:1. x The specific surface area of ​​the TiO2@C material is 66.04 m 2 / g, pore size is 5.2nm.

[0139] Embodiment 3:

[0140] The difference between Example 3 and Example 1 is that (1.3) Ti3C2T x / TiO2@C in the preparation of Ti3C2Tx The mass ratio of Ti3C2T to MIL-125 is 0.2:1. x The specific surface area of ​​the TiO2@C material is 55.69 m 2 / g, pore size is 9.8nm.

[0141] Embodiment 4:

[0142] The difference between Example 4 and Example 1 is that (1.3) Ti3C2T x / TiO2@C in the preparation of Ti3C2T x The mass ratio of Ti3C2T to MIL-125 is 0.4:1. x The specific surface area of ​​TiO2@C material is 37.23 m 2 / g, and the pore size is 18.4nm.

[0143] Embodiment 5:

[0144] The difference between Example 5 and Example 1 is that (1.3) Ti3C2T x / TiO2@C in the preparation of Ti3C2T x The mass ratio of Ti3C2T to MIL-125 is 0.5:1. x The specific surface area of ​​the TiO2@C material is 26.92 m 2 / g, pore size is 20.1nm.

[0145] Embodiment 6~9:

[0146] The difference between Examples 6 to 9 and Example 1 is that the thickness L1 of the negative electrode protective layer and the ratio L1 / L2 are different. In Example 6, the thickness L1 of the negative electrode protective layer is 5 μm, and L1 / L2 is 0.05. In Example 7, the thickness L1 of the negative electrode protective layer is 20 μm, and L1 / L2 is 0.2. In Example 8, the thickness L1 of the negative electrode protective layer is 30 μm, and L1 / L2 is 0.3. In Example 9, the thickness L1 of the negative electrode protective layer is 40 μm, and L1 / L2 is 0.4.

[0147] Comparative Example 1:

[0148] The difference between Comparative Example 1 and Example 1 is that the negative electrode sheet of Comparative Example 1 does not contain a negative electrode protection layer. The thickness of the negative electrode active material layer is 90 μm.

[0149] Comparative Example 2:

[0150] The difference between Comparative Example 2 and Example 1 is that in the preparation of the negative electrode sheet in (2) of Comparative Example 2, Ti3C2T x / TiO2@C material was replaced by Ti3C2T prepared by (1.1) x, Ti3C2T x The specific surface area of ​​the material is 16.52m 2 / g, pore size is 21.5nm.

[0151] Comparative Example 3:

[0152] The difference between Comparative Example 3 and Example 1 is that in the preparation of the negative electrode sheet in (2) of Comparative Example 3, Ti3C2T x / TiO2@C material was replaced by TiO2@C material. The preparation of TiO2@C material was as follows: MIL-125 was pyrolyzed at 500 °C (heating rate 5 °C / min) in Ar atmosphere to obtain TiO2@C. The specific surface area of ​​TiO2@C material was 103.67 m 2 / g, and the pore size is 4.1nm.

[0153] Test part:

[0154] Negative electrode sheet thickness test: The cold pressed negative electrode sheet was cut into 6cm*6cm samples, and then polished with IB-19500CP ion cross-section polisher to obtain polished samples with cut surfaces. Then, the samples were tested with ZEISS sigma 300 equipment in accordance with standard JY / T010-1996. Ten different positions were randomly selected from the test samples for testing, and the average value was taken to obtain the total thickness of the negative electrode protective layer, the negative electrode film layer, and the ratio of the thickness of the negative electrode protective layer to the total thickness of the negative electrode film layer.

[0155] Negative electrode sheet rebound rate test: Use a micrometer to measure the thickness h0 of a newly made negative electrode sheet (not subjected to cycle test). Then use the sheet to prepare a secondary battery.

[0156] The newly made secondary battery is charged to 4.25V at 1 / 3C constant current, then charged to 0.1C at 4.25V constant voltage, and then discharged to 2.5V at 0.33C to complete a cycle. After repeating the cycle for 400cls, the cell is charged to 4.25V. At this time, the battery is fully charged (the voltage window is 2.5V-4.25V). Then it is disassembled, the fully charged negative electrode plate is taken out, and the thickness of the negative electrode plate at this time is measured with a micrometer (h1). The plate rebound rate = (h1 / h0-1)×100%

[0157] Energy density test: At 25°C, charge to 4.25V at 0.33C standard, charge to 0.05C at 4.25V constant voltage, let stand for 10 minutes, discharge to 2.5V at 0.33C, record the discharge capacity, and then calculate the energy density during discharge. Energy density (Wh / kg) = discharge capacity (Wh) / secondary battery mass (kg).

[0158] Cycling performance test: At 25°C, charge the secondary battery to 4.25V at 1 / 3C constant current, then charge at 4.25V constant voltage to a current of 0.05C, leave for 5 minutes, and then discharge to 2.5V at 1 / 3C. The measured capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time. Then, after n cycles (i.e., n turns (cls)), the battery capacity retention rate Pn = Cn / C0*100%.

[0159] Cyclic DCR growth test: At 25°C, charge the newly made secondary battery to 4.25V at 1 / 3C constant current, then charge at 4.25V constant voltage to a current of 0.05C, and then discharge at 1 / 3C to 2.5V. Extract the voltage change before and after 30s at the beginning of discharge as ΔU, and the current change before and after as ΔI, and obtain the discharge DCR value = ΔU / ΔI, and measure the DCR value D0 of this charging process, and leave it for 5min. Repeat the above steps for the same battery, and record the DCR value D1 of the battery after the nth cycle at the same time, then the DCR growth rate Dn after n cycles (i.e., n circles (cls)) = Dn / D0*100%.

[0160] The electrochemical performance test data of the secondary batteries of Examples 1 to 9 and Comparative Examples 1 to 3 are all recorded in Table 1.

[0161] Table 1 Composition and electrochemical performance of secondary batteries of Examples 1 to 9 and Comparative Examples 1 to 3

[0162]

[0163]

[0164] It can be seen from the relevant data in Table 1 that the energy density of the secondary batteries of Examples 1 to 9 is 225Wh / kg to 231Wh / kg, the capacity retention rate after 400cls cycle is 98.7% to 99.4%, the negative electrode sheet rebound rate is 26% to 38%, and the DCR growth rate is 105% to 114%; while ensuring a high energy density, the secondary batteries of Examples 1 to 9 have a high 400cls cycle capacity retention rate, a small negative electrode sheet rebound rate, a small secondary battery DCR growth rate, and good cycle performance.

[0165] In the secondary battery of Comparative Example 1, the negative electrode sheet is not provided with a negative electrode protective layer, the energy density of the secondary battery is 232Wh / kg, the capacity retention rate after 400cls cycle is 96.5%, the negative electrode sheet rebound rate is 41%, and the DCR growth rate is 127%. The secondary battery of Comparative Example 1 is not provided with a negative electrode protective layer, and the energy density of the secondary battery is slightly higher than that of the secondary batteries of Examples 1 to 9, but the cycle capacity retention rate of Comparative Example 1 is lower than that of Examples 1 to 9, and the negative electrode sheet rebound rate and the secondary battery DCR growth rate of Comparative Example 1 are both higher than those of Examples 1 to 9, which shows that the cycle of the secondary battery of Comparative Example 1 is significantly deteriorated, and the cycle performance is significantly inferior to that of the secondary batteries of Examples 1 to 9.

[0166] In the secondary batteries of Comparative Examples 2 and 3, the negative electrode protective layers have the following components: Ti3C2T x The cycle performance of the secondary batteries of Comparative Examples 2 to 3 is slightly better than that of the secondary battery of Comparative Example 1, but inferior to that of the secondary batteries of Examples 1 to 9.

[0167] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0168] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the attached claims described in the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description and drawings can be used to explain the content of the claims.

Claims

1. A negative electrode plate, characterized in that: include: Anode current collector; a negative electrode active material layer, the negative electrode active material layer being disposed on at least one surface of the negative electrode current collector; and A negative electrode protection layer, wherein the negative electrode protection layer is arranged on the surface of the negative electrode active material layer away from the negative electrode current collector; the negative electrode protection layer comprises a composite carbon material; the composite carbon material comprises a MXene material and a three-dimensional inorganic carbon material, and the three-dimensional inorganic carbon material contains a metal oxide.

2. The negative electrode sheet according to claim 1, characterized in that: The MXene material includes Ti3C2T x 、Ti4C3Tx、Ti2CT x 、V2CT x and Nb2CT x At least one of which T x represents the functional group of MXene material, T x Including -OH.

3. The negative electrode sheet according to claim 2, characterized in that: T x It also includes at least one of =O, -F and -Cl.

4. The negative electrode sheet according to claim 2, characterized in that: The three-dimensional inorganic carbon material contains a carboxyl group, and the MXene material is connected to the three-dimensional inorganic carbon material through an ester bond.

5. The negative electrode sheet according to claim 1, characterized in that: The specific surface area of ​​the composite carbon material is 26 m 2 / g~67m 2 / g.

6. The negative electrode sheet according to claim 5, characterized in that: The specific surface area of ​​the composite carbon material is 26.92 m 2 / g~66.04m 2 / g.

7. The negative electrode sheet according to claim 1, characterized in that: The pore diameter of the composite carbon material is 5nm-21nm.

8. The negative electrode sheet according to claim 7, characterized in that: The pore diameter of the composite carbon material is 5.2nm-20.1nm.

9. The negative electrode sheet according to claim 1, characterized in that: The metal oxide includes at least one of TiO2, ZnO, Fe3O4, Cr2O3, ZrO2 and CuO.

10. The negative electrode sheet according to claim 9, characterized in that: The metal oxide is TiO2.

11. The negative electrode sheet according to claim 1, characterized in that: In the negative electrode protection layer, the mass percentage of the composite carbon material is 90% to 98%.

12. The negative electrode sheet according to claim 11, characterized in that: In the negative electrode protection layer, the mass percentage of the composite carbon material is 96% to 97.5%.

13. The negative electrode sheet according to any one of claims 1 to 12, characterized in that: The raw materials for preparing the composite carbon material include the MXene material and the metal organic framework material.

14. The negative electrode sheet according to claim 13, characterized in that: The mass ratio of the MXene material to the metal organic framework material is (0.1-0.5):

1.

15. The negative electrode sheet according to claim 14, characterized in that: The mass ratio of the MXene material to the metal organic framework material is (0.2-0.4):

1.

16. The negative electrode sheet according to claim 13, characterized in that: The metal center of the metal organic framework material includes at least one of Ti, Fe, Cu, Zr, Zn and Cr.

17. The negative electrode sheet according to claim 16, characterized in that: The metal center is Ti.

18. The negative electrode sheet according to claim 13, characterized in that: The organic ligand of the metal organic framework material includes at least one of terephthalic acid and trimesic acid.

19. The negative electrode sheet according to claim 18, characterized in that: The organic ligand is terephthalic acid.

20. The negative electrode sheet according to claim 13, characterized in that: The metal organic framework material includes at least one of MIL-125, MOF-5, MIL-88B, MIL-100, MIL-101, UiO-66 and HKUST-1.

21. The negative electrode sheet according to claim 20, characterized in that: The metal organic framework material is MIL-125.

22. The negative electrode plate according to claim 13, characterized in that: The preparation method of the composite carbon material comprises the following steps: Mixing the MXene material and the metal organic framework material to prepare an intermediate; The intermediate is pyrolyzed at 250° C. to 500° C. under a protective atmosphere to prepare the composite carbon material.

23. The negative electrode sheet according to any one of claims 1 to 12, characterized in that: The thickness of the negative electrode protection layer is L1, the total thickness of the negative electrode protection layer and the negative electrode active material layer is L2, and the negative electrode plate satisfies: 0.05≤L1 / L2≤0.

4.

24. The negative electrode sheet according to any one of claims 1 to 12, characterized in that: The thickness L1 of the negative electrode protection layer is 8 μm to 15 μm.

25. The negative electrode sheet according to claim 24, characterized in that: The thickness L1 of the negative electrode protection layer is 10 μm to 14 μm.

26. The method for preparing a negative electrode sheet according to any one of claims 1 to 25, characterized in that: The following steps are involved: preparing a negative electrode protective layer slurry, wherein the negative electrode protective layer slurry contains the composite carbon material; The negative electrode protection layer slurry is used to form the negative electrode protection layer on the surface of the negative electrode active material layer away from the negative electrode current collector.

27. A secondary battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet as described in any one of claims 1 to 25.

28. A battery module, characterized in that: Includes the secondary battery as claimed in claim 27.

29. A battery pack, characterized in that: Includes at least one of the secondary battery according to claim 27 and the battery module according to claim 28.

30. An electrical device, characterized in that: The battery comprises at least one selected from the group consisting of the secondary battery of claim 27, the battery module of claim 28, and the battery pack of claim 29.

Citation Information

Patent Citations

  • Lithium metal negative electrode and preparation method thereof and lithium metal battery

    CN113964290A

  • Three-dimensional structure MXene / SnO2 / C negative electrode composite material and preparation method thereof

    CN114039051A